1986
DOI: 10.1007/bf00315367
|View full text |Cite
|
Sign up to set email alerts
|

Thermodilution measurement of right ventricular ejection fraction with a modified pulmonary artery catheter

Abstract: In 14 critically ill patients in stable cardiopulmonary status, right ventricular ejection fraction (RVEF) was measured by thermodilution technique and by radionuclear (gated first pass) technique. The pulmonary artery catheter was equipped with a fast-response thermistor and an intracardiac ECG monitor. In addition, the proximal lumen ended in a 3-hole port 21 cm from the tip of the catheter to facilitate mixing of the cold bolus above the tricuspid valve. The use of a new algorithm based on an exponential cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
3

Year Published

1992
1992
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(39 citation statements)
references
References 9 publications
0
36
0
3
Order By: Relevance
“…[23][24][25][26] However, the relative contribution of the right ventricle to septic cardiomyopathy remains unknown.…”
Section: Characteristics Of Myocardial Dysfunction In Sepsismentioning
confidence: 99%
“…[23][24][25][26] However, the relative contribution of the right ventricle to septic cardiomyopathy remains unknown.…”
Section: Characteristics Of Myocardial Dysfunction In Sepsismentioning
confidence: 99%
“…RV pressure was monitored with a micromanometer catheter (Millar Instruments; Houston, TX) and instantaneous pulmonary blood flow with a transit-time ultrasonic flow probe (Transonic Systems; Ithaca, NY). Cardiac output and RV ejection fraction were measured with a fast-response thermodilution pulmonary artery catheter (Baxter-Edwards; Irvine, CA) (30). A clamp was placed around the pulmonary artery upstream from the flow probe, ϳ1 cm away from the pulmonary valve.…”
Section: Preparationmentioning
confidence: 99%
“…Calculation of the ratio between the tempera ture decreases of two successive diastolic plateaus yields an estimate of the residual fraction (RF) of the RV. The EF is then calculated as: EF = 1 -RF [5,6,14], Cardiac output is calculated from the same pulmonary artery temperature curve by using the Stewart-Hamilton equation [14] and cardiac output divided by heart rate yields the stroke volume (SV). Using heart rate and EF.…”
Section: Thermodilution Studiesmentioning
confidence: 99%
“…Several studies comparing thermodilution measurements with bi plane angiographic data showed the usefulness of this method for the determination of RV volumes and EF in Received: August 22. 1994 Accepted: September 7.1994 patients with various cardiac diseases [5][6][7], However, limitations of angiographic RV volume measurements include impaired sharpness of ventricular contours due to trabeculations, variable spatial orientation of the RV, and the lack of a single geometric reference model to fit all possible ventricular shapes [8,9], Magnetic resonance imaging (MRI) can be regarded as an alternative imaging modality allowing volume quantif ication of both the RV and the LV and is now being con sidered as the gold standard for volume quantification in vivo [10][11][12], Thus, the purpose of our study was to validate the accuracy of a thermodilution technique for RV volume quantification using simultaneous MRI in patients with dilated cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%